If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (x + 2) * 2 + 2 Reorder the terms: y = (2 + x) * 2 + 2 Reorder the terms for easier multiplication: y = 2(2 + x) + 2 y = (2 * 2 + x * 2) + 2 y = (4 + 2x) + 2 Reorder the terms: y = 4 + 2 + 2x Combine like terms: 4 + 2 = 6 y = 6 + 2x Solving y = 6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 6 + 2x
| 2c+2c+2+c=107 | | 6x^2+14x-30=0 | | 2/7f=5/7 | | X/2=0.6 | | 525+.21c=585+.13c | | 2c+10+c+10+c=107 | | x+1(x-4)=x-5(x+4) | | y=-5/7x5-5 | | 5x+10x-7x-5= | | 2(8x+1)=5(3x+1) | | 6x^2-16x-30=0 | | -400x+4000=2400 | | a-5-(-2)=7-q | | -3/10p=3/10 | | 3x=195 | | Y-26=34 | | 4a-9a+3=-32 | | -356=7(z-8) | | 7/3x=21 | | 4a+9a+3=-32 | | 10x-14xy= | | 13*17/1/3 | | 8/14z=6/8 | | 3.14=c/d | | -8+x+6x=-34 | | -17=3a-8 | | Y-6=-1 | | 4.5(3)+4.5x=24.75 | | 7(n+5)+3(n-1)= | | a+9-2a=6 | | 8(r+7)=56 | | -5x+40=6-70 |